2022
DOI: 10.25518/0037-9565.10857
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical quality of the Medjerda River in Tunisia and suitability for irrigation during the moist and the dry seasons

Abstract: Surface waters are usually exposed to industrial, urban, and agricultural wastes. This study assessed the water and the sediments quality of the important primary watercourse in Tunisia and the principal source of domestic and irrigation purposes, the Medjerda River. Water samples were analyzed for total suspended solids, calcium, magnesium, total hardness, carbonates, bicarbonates, residual sodium hazard, and magnesium hazard. They were collected from five sampling sites along the Medjerda watercourse from up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…For these reasons, these anthropogenic activities are the main drivers for high enrichment and contamination indices, as also reported by Napoletano et al [23]. Particularly interesting is also the comparison with the results of Ben Ayed et al [61], who reported particularly high contamination with Pb and Cd in five industrial areas along the Medjerda River. In addition, URB was the second most polluting land use due to it being affected by vehicular emissions and open burnings that released contaminants, especially Pb [62].…”
Section: Impact Of Land Uses On Soil and Watersupporting
confidence: 73%
“…For these reasons, these anthropogenic activities are the main drivers for high enrichment and contamination indices, as also reported by Napoletano et al [23]. Particularly interesting is also the comparison with the results of Ben Ayed et al [61], who reported particularly high contamination with Pb and Cd in five industrial areas along the Medjerda River. In addition, URB was the second most polluting land use due to it being affected by vehicular emissions and open burnings that released contaminants, especially Pb [62].…”
Section: Impact Of Land Uses On Soil and Watersupporting
confidence: 73%